2008
DOI: 10.1016/j.jasms.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oligonucleotide gas-phase conformers: H/D exchange and ion mobility as complementary techniques

Abstract: Gas-phase hydrogen/deuterium exchange of small oligonucleotides (dTG, dC 6 and C 6 ) with CD 3 0D was performed in the second hexapole of a Fourier transform ion-cyclotron resonance (FTICR) mass spectrometer. Ion activation experiments were conducted by accelerating the ions at the entrance of the H/D exchange cell under conditions promoting exclusively collisional isomerization. These experiments allowed us to assess the presence of several conformers, and to probe the height of the isomerization barrier sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Purves and co-workers showed that each individual technique could identify only 2 conformers for the [M+2H] 2+ ion of bradykinin while 4 conformers were characterized by combining both methods. Complementary information can also be gathered by combining low-field ion mobility (either with a drift tube or a T-Wave instrument) and gas-phase HDX, as shown for oligonucleotides [117]. Finally, a recent setup consisted of a combination of low-field ion mobility and solution HDX.…”
Section: Ion Mobility and Hdxmentioning
confidence: 99%
“…Purves and co-workers showed that each individual technique could identify only 2 conformers for the [M+2H] 2+ ion of bradykinin while 4 conformers were characterized by combining both methods. Complementary information can also be gathered by combining low-field ion mobility (either with a drift tube or a T-Wave instrument) and gas-phase HDX, as shown for oligonucleotides [117]. Finally, a recent setup consisted of a combination of low-field ion mobility and solution HDX.…”
Section: Ion Mobility and Hdxmentioning
confidence: 99%
“…However, this approach has been successfully employed to highlight the protein surfaces in contact with them and to study the dynamics associated with the specific interactions [163][164][165]. The implementation of HDX in the gas phase has been demonstrated for nucleotides [166,167], unstructured oligonucleotides [168], and relatively small structured constructs [169,170], but its application to the larger assemblies has yet to be reported.…”
Section: Elucidating Structure-function Relationshipsmentioning
confidence: 99%
“…The conformational study of progressively larger assemblies will be expected to take full advantage of recent exciting developments in ion mobility mass spectrometry, which has been already shown to be capable of affording direct information about nucleic acid structures in the gas phase [169,176].…”
Section: Elucidating Structure-function Relationshipsmentioning
confidence: 99%
“…In recent years, these studies have been augmented by extensive molecular modeling in an effort to provide further support for mechanistic and structural details of the H/D exchange reactions of small organic molecules [13,6,8,9,14,17,24], as well as affording incredible insight into the gas-phase conformations of biological molecules, such as proteins and DNA [11,20,25,28,29]. The gas-phase structures of mononucleotides and dinucleotides [4,5,12,13,15,23], in addition to some large oligonucleotides [7,11,20,25,27,], have been examined by H/D exchange methods in a number of studies using different deuterating reagents and types of mass spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase H/D exchange experiments [26,27] and ion mobility measurements of dinucleotides have also been reported [31,32]. The ion mobility studies concluded that multiple gas-phase conformations of similar energy existed and that the conformations were both nucleobase- and sequence-dependent.…”
Section: Introductionmentioning
confidence: 99%